Antibacterial ceramic tile and its preparation method and application
By using porous silica-coated zinc oxide and nano silver in ceramic tiles, the balance between antibacterial properties and hydrophobic and antifouling properties of ceramic tiles is solved, and the good antibacterial durability and anti-fouling properties of ceramic tiles are achieved. Dirty effect.
Patent Information
- Application Number
- CN202411406176.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-10
AI Technical Summary
When existing ceramic tiles improve antibacterial properties, they can easily lead to reduced hydrophobic and antifouling properties, and the antibacterial effect is not durable and the antibacterial components are easily lost.
Using a combination of porous silica-coated zinc oxide and nanosilver, by adding porous silica-coated zinc oxide to the glaze layer, and using silver nitrate solution, sodium citrate solution and fluorine-containing compounds in the coating. Nanosilver is formed by thermal curing, which improves the overall antibacterial performance and durability of ceramic tiles, while enhancing hydrophobic and antifouling properties.
It achieves good antibacterial performance and durability of ceramic tiles, ensures the durability of antibacterial effects, and improves hydrophobic and anti-fouling properties, ensuring the effectiveness of ceramic tiles in practical applications.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramics, and in particular relates to an antibacterial ceramic tile and a preparation method and application thereof. Background Art
[0002] At present, most of the research on ceramic tiles obtains antibacterial properties through two ways: one is to add antibacterial ingredients to wax water and give ceramic tiles antibacterial properties by waxing; the other is to add antibacterial agents to ceramic glazes and prepare ceramic tiles with antibacterial properties by firing. However, both methods have certain defects. The antibacterial ingredients are introduced into the surface of ceramic tiles by waxing, mainly by using the microporous structure on the surface of ceramic tiles to inject the antibacterial ingredients into the microporous structure, thereby having a certain antibacterial effect. However, if the surface of the ceramic tile is relatively flat, it is difficult for the antibacterial ingredients to adhere to the surface of the ceramic tile, thereby failing to effectively improve the antibacterial properties of the ceramic tile. If the microporous structure is too much / too large, the hydrophobic and antifouling properties will be reduced, and the antibacterial effect of this method is not durable, and it is easy to cause the loss of antibacterial ingredients after grinding and brushing. By adding antibacterial ingredients to the polishing glaze to give ceramic tiles antibacterial properties, good antibacterial properties can be effectively maintained, and the antibacterial properties are well maintained. However, due to the high content of glass phase in the transparent glaze during the firing process, it is easy to wrap the antibacterial ingredients and reduce the antibacterial effect of the ceramic tile.
[0003] Therefore, it is very necessary to provide a ceramic tile with good antibacterial and antifouling properties. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides an antibacterial ceramic tile and a preparation method and application thereof, wherein the ceramic tile can simultaneously have good overall antibacterial performance, antibacterial durability and antifouling performance.
[0005] In a first aspect, the present invention provides an antibacterial ceramic tile, which comprises a body layer, a glaze layer and a coating layer from bottom to top;
[0006] The raw materials for preparing the glaze layer include porous silicon dioxide coated zinc oxide;
[0007] The coating is formed by heat curing a mixed solution containing a silver nitrate solution, a sodium citrate solution and a fluorine-containing compound;
[0008] The porous silica-coated zinc oxide is prepared by a preparation method comprising the following steps:
[0009] mixing zinc oxide, an organic solvent and an organosiloxane to obtain an oil phase;
[0010] mixing an emulsifier, a porogen and water to obtain an aqueous phase;
[0011] The oil phase is added to the water phase, emulsified, the pH value is adjusted to alkaline, heated, stirred and reacted to obtain porous silica-coated zinc oxide.
[0012] Specifically, the present invention utilizes porous silica to coat zinc oxide, which can effectively protect the antibacterial property of zinc oxide during the firing process to form a glaze layer, delay or prevent the corrosion of zinc oxide by the original silicate system of the ceramic tile glaze during high-temperature firing, thereby causing the zinc oxide to fail, thereby ensuring that the prepared ceramic tile can achieve the expected antibacterial effect in practical applications, and at the same time, the porous structure allows zinc oxide to have space to contact bacteria, so under the premise of protecting zinc oxide, the antibacterial effect of zinc oxide is not affected; in addition, the surface of the porous silica has an irregular porous structure, which has an electrostatic adsorption effect on the silver ions of silver nitrate, so that the nano-silver formed by the heating reduction of the silver nitrate can be evenly distributed on the surface and internal voids of the porous silica, so that the porous silica-coated zinc oxide has stronger antibacterial properties, and the nano-element silver particles are small, the surface effect and size effect are significant, and the antibacterial activity is very strong, and the antibacterial property is significantly improved under the joint action of zinc oxide and nano-silver. The silicon-oxygen bonds of the fluorine-containing compounds in the coating of the present invention interact with the hydroxyl groups on the surface of the porous silica and the silicon-oxygen bonds on the surface of the glaze layer, react and solidify, thereby improving the bonding force between the glaze layer and the coating, making the coating less likely to fall off, thereby improving the overall antibacterial durability of the ceramic tile.
[0013] In some embodiments of the present invention, the concentration of the silver nitrate solution is 0.001-0.003 mol / L.
[0014] In some embodiments of the present invention, the concentration of the silver nitrate solution is 0.001-0.002 mol / L.
[0015] In some embodiments of the present invention, the mass fraction of the sodium citrate solution is 1-3%.
[0016] In some embodiments of the present invention, the mass fraction of the sodium citrate solution is 1-2%.
[0017] In some embodiments of the present invention, the volume ratio of the silver nitrate solution, the sodium citrate solution and the fluorine-containing compound is 100:(1-3):(300-500).
[0018] In some embodiments of the present invention, the raw materials for preparing the glaze layer further include ceramic glaze. The ceramic glaze can be conventional ceramic glaze, which is not limited in the present invention.
[0019] In some embodiments of the present invention, the mass ratio of the porous silica-coated zinc oxide to the ceramic glaze is 1:(5-10).
[0020] In some embodiments of the present invention, the raw materials for preparing the coating further include a diluent.
[0021] In some embodiments of the invention, the diluent comprises ethanol.
[0022] In some embodiments of the present invention, the mass ratio of the diluent to other raw materials for preparing the coating is (10-50): 1. The other raw materials for preparing the coating refer to silver nitrate solution, sodium citrate solution and fluorine-containing compounds.
[0023] In some embodiments of the present invention, the mass ratio of zinc oxide, organosiloxane, emulsifier and porogen is (10-12):(18-20):(0.5-1):1.
[0024] In some embodiments of the present invention, the fluorine-containing compound includes at least one of perfluorooctyltriethoxysilane, heptadecafluorodecyltrimethoxysilane, trifluoropropoxysilane, dual-terminal hydroxyl fluorinated polysiloxane and dodecafluoroheptylpropyltrimethoxysilane.
[0025] In some embodiments of the present invention, the organic solvent includes at least one of dichloromethane, ethanol, butanol, ethylene glycol methyl ether and propylene glycol methyl ether.
[0026] In some embodiments of the present invention, the organosiloxane includes at least one of ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate and butyl orthosilicate.
[0027] In some embodiments of the present invention, the emulsifier includes at least one of Tween-20, Tween-40, Tween-60 and Tween-80.
[0028] In some embodiments of the present invention, the porogen includes at least one of hexadecyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride and hexadecyltrimethylsodium bromide.
[0029] In some embodiments of the present invention, the alkaline pH value is 9-10.
[0030] In some embodiments of the present invention, the heating temperature is 40-45° C.; and the stirring reaction time is 5-7 h.
[0031] In some embodiments of the present invention, after the stirring reaction, the steps of centrifuging, washing and drying the product are also included.
[0032] The second aspect of the present invention provides a method for preparing the antibacterial ceramic tile according to the first aspect of the present invention, comprising the following steps:
[0033] preparing a glaze slurry containing porous silica-coated zinc oxide;
[0034] Applying the glaze slurry on the green body layer, drying and firing to form a glaze layer;
[0035] mixing the silver nitrate solution, the sodium citrate solution and the fluorine-containing compound to obtain a mixed solution;
[0036] The mixed liquid is applied to the surface of the glaze layer and thermally cured to form a coating to obtain the antibacterial ceramic tile.
[0037] In some embodiments of the present invention, the temperature of the thermal curing is 100-200°C.
[0038] In some embodiments of the present invention, the thermal curing time is 1-3 hours.
[0039] In some embodiments of the present invention, the method further comprises the step of polishing the glaze layer.
[0040] In some embodiments of the present invention, a diluent is further added to dilute the mixture.
[0041] In some embodiments of the present invention, the sintering temperature is 1180-1250°C.
[0042] In some embodiments of the present invention, the sintering time is 50-60 minutes.
[0043] The third aspect of the present invention provides the use of the antibacterial ceramic brick described in the first aspect of the present invention in the field of construction.
[0044] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0045] (1) The present invention adds porous silica-coated zinc oxide to the glaze layer. The porous silica can protect the zinc oxide therein. At the same time, the porous structure allows the zinc oxide to have space to contact with bacteria, thereby not affecting the antibacterial effect of the zinc oxide. At the same time, the surface of the porous silica has an irregular porous structure, which has an electrostatic adsorption effect on the silver ions of silver nitrate, so that the nanosilver formed by the silver nitrate in the coating raw material can be evenly distributed on the surface and internal gaps of the silica, so that the porous silica-coated zinc oxide has stronger antibacterial properties. In addition, since the antibacterial materials (porous silica-coated zinc oxide and nanosilver) are distributed more evenly, the antibacterial effect of each point on the surface of the ceramic tile is more uniform, and the overall antibacterial property is good.
[0046] (2) The silicon-oxygen bonds of the fluorine-containing compounds in the coating of the present invention interact with the hydroxyl groups on the surface of the porous silica and the silicon-oxygen bonds on the surface of the glaze layer, react and solidify, thereby improving the bonding strength between the glaze layer and the coating, making the coating less likely to fall off, thereby improving the overall antibacterial durability of the ceramic tile. At the same time, the fluorine-containing compounds have a certain hydrophobicity, which makes the ceramic tile also have hydrophobic and anti-fouling properties. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0048] Example 1: Antibacterial ceramic brick and its preparation
[0049] An antibacterial ceramic tile comprises, from bottom to top, a body layer, a glaze layer and a coating layer, wherein the raw materials for preparing the glaze layer include porous silicon dioxide coated zinc oxide and ceramic glaze, and the raw materials for preparing the coating layer include silver nitrate solution, sodium citrate solution, perfluorooctyl triethoxysilane and ethanol;
[0050] The concentration of the silver nitrate solution is 0.001 mol / L, the mass fraction of the sodium citrate solution is 1%, and the volume ratio of the silver nitrate solution, the sodium citrate solution and perfluorooctyltriethoxysilane is 100:2:400;
[0051] The porous silicon dioxide coated zinc oxide is prepared by a preparation method comprising the following steps:
[0052] (1) 10 parts by weight of nano zinc oxide was uniformly dispersed in 200 parts by weight of dichloromethane, and then 18 parts by weight of ethyl orthosilicate was added, and the mixture was stirred for 10 minutes to obtain an oil phase;
[0053] (2) dissolving 0.5 parts by weight of Tween-20 and 1 part by weight of hexadecyltrimethylammonium bromide in 500 parts by weight of water to obtain an aqueous phase;
[0054] (3) The oil phase was added dropwise into the water phase, emulsified at 6000 r / min for 15 min, the pH value was adjusted to 9, heated to 40°C, stirred for reaction for 5 h, centrifuged, washed, and dried to obtain porous silica-coated zinc oxide.
[0055] The method for preparing the antibacterial ceramic brick in this example comprises the following steps:
[0056] (1) The porous silica-coated zinc oxide and the ceramic glaze were mixed in a mass ratio of 1:7, and then ball-milled with water for 20 minutes to obtain a glaze slurry;
[0057] (2) applying the glaze slurry obtained in step (1) on the green body layer, drying it, firing it in a kiln at 1200° C. for 60 min to form a glaze layer, and polishing the surface;
[0058] (3) mixing the silver nitrate solution, the sodium citrate solution and perfluorooctyltriethoxysilane, stirring evenly, and then adding ethanol for dilution (the mass ratio of other raw materials to ethanol is 1:20) to obtain a mixed solution;
[0059] (4) The mixed solution obtained in step (3) is applied to the surface of the polished glaze layer in step (2), and is thermally cured at 150° C. for 1 hour to form a coating to obtain an antibacterial ceramic tile.
[0060] Example 2: Antibacterial ceramic brick and its preparation
[0061] An antibacterial ceramic tile comprises, from bottom to top, a body layer, a glaze layer and a coating layer, wherein the raw materials for preparing the glaze layer include porous silicon dioxide coated zinc oxide and ceramic glaze, and the raw materials for preparing the coating layer include silver nitrate solution, sodium citrate solution, perfluorooctyl triethoxysilane and ethanol;
[0062] The concentration of the silver nitrate solution is 0.001 mol / L, the mass fraction of the sodium citrate solution is 1%, and the volume ratio of the silver nitrate solution, the sodium citrate solution and perfluorooctyltriethoxysilane is 100:2:400;
[0063] The porous silicon dioxide coated zinc oxide is prepared by a preparation method comprising the following steps:
[0064] (1) 10 parts by weight of nano zinc oxide was uniformly dispersed in 200 parts by weight of dichloromethane, and then 18 parts by weight of ethyl orthosilicate was added, and the mixture was stirred for 10 minutes to obtain an oil phase;
[0065] (2) dissolving 0.5 parts by weight of Tween-40 and 1 part by weight of hexadecyltrimethyl sodium bromide in 500 parts by weight of water to obtain an aqueous phase;
[0066] (3) The oil phase was added dropwise into the water phase, emulsified at 6000 r / min for 15 min, the pH value was adjusted to 9, heated to 40°C, stirred for reaction for 5 h, centrifuged, washed, and dried to obtain porous silica-coated zinc oxide.
[0067] The method for preparing the antibacterial ceramic brick in this example comprises the following steps:
[0068] (1) The porous silica-coated zinc oxide and the ceramic glaze were mixed in a mass ratio of 1:8, and then ball-milled with water for 20 minutes to obtain a glaze slurry;
[0069] (2) applying the glaze slurry obtained in step (1) on the green body layer, drying it, firing it in a kiln at 1200° C. for 60 min to form a glaze layer, and polishing the surface;
[0070] (3) mixing the silver nitrate solution, the sodium citrate solution and perfluorooctyltriethoxysilane, stirring evenly, and then adding ethanol for dilution (the mass ratio of other raw materials to ethanol is 1:20) to obtain a mixed solution;
[0071] (4) The mixed solution obtained in step (3) is applied to the surface of the polished glaze layer in step (2), and is thermally cured at 150° C. for 1 hour to form a coating to obtain an antibacterial ceramic tile.
[0072] Example 3: Antibacterial ceramic brick and its preparation
[0073] An antibacterial ceramic tile comprises, from bottom to top, a body layer, a glaze layer and a coating layer, wherein the raw materials for preparing the glaze layer include porous silicon dioxide coated zinc oxide and ceramic glaze, and the raw materials for preparing the coating layer include silver nitrate solution, sodium citrate solution, perfluorooctyl triethoxysilane and ethanol;
[0074] The concentration of the silver nitrate solution is 0.001 mol / L, the mass fraction of the sodium citrate solution is 1%, and the volume ratio of the silver nitrate solution, the sodium citrate solution and perfluorooctyltriethoxysilane is 100:2:400;
[0075] The porous silicon dioxide coated zinc oxide is prepared by a preparation method comprising the following steps:
[0076] (1) 12 parts by weight of nano zinc oxide was uniformly dispersed in 200 parts by weight of dichloromethane, and then 20 parts by weight of methyl orthosilicate was added, and the mixture was stirred for 10 minutes to obtain an oil phase;
[0077] (2) dissolving 1 part by weight of Tween-20 and 1 part by weight of cetyltrimethylammonium bromide in 500 parts by weight of water to obtain an aqueous phase;
[0078] (3) The oil phase was added dropwise into the water phase, emulsified at 6000 r / min for 15 min, the pH value was adjusted to 9, heated to 40°C, stirred for reaction for 5 h, centrifuged, washed, and dried to obtain porous silica-coated zinc oxide.
[0079] The method for preparing the antibacterial ceramic brick in this example comprises the following steps:
[0080] (1) The porous silica-coated zinc oxide and the ceramic glaze were mixed in a mass ratio of 1:7, and then ball-milled with water for 20 minutes to obtain a glaze slurry;
[0081] (2) applying the glaze slurry obtained in step (1) on the green body layer, drying it, firing it in a kiln at 1200° C. for 60 min to form a glaze layer, and polishing the surface;
[0082] (3) mixing the silver nitrate solution, the sodium citrate solution and perfluorooctyltriethoxysilane, stirring evenly, and then adding ethanol for dilution (the mass ratio of other raw materials to ethanol is 1:20) to obtain a mixed solution;
[0083] (4) The mixed solution obtained in step (3) is applied to the surface of the polished glaze layer in step (2), and is thermally cured at 150° C. for 1 hour to form a coating to obtain an antibacterial ceramic tile.
[0084] Example 4: Antibacterial ceramic brick and its preparation
[0085] An antibacterial ceramic tile comprises, from bottom to top, a body layer, a glaze layer and a coating layer, wherein the raw materials for preparing the glaze layer include porous silicon dioxide coated zinc oxide and ceramic glaze, and the raw materials for preparing the coating layer include silver nitrate solution, sodium citrate solution, perfluorooctyl triethoxysilane and ethanol;
[0086] The concentration of the silver nitrate solution is 0.001 mol / L, the mass fraction of the sodium citrate solution is 1%, and the volume ratio of the silver nitrate solution, the sodium citrate solution and perfluorooctyltriethoxysilane is 100:2:400;
[0087] The porous silicon dioxide coated zinc oxide is prepared by a preparation method comprising the following steps:
[0088] (1) 10 parts by weight of nano zinc oxide was uniformly dispersed in 200 parts by weight of dichloromethane, and then 18 parts by weight of ethyl orthosilicate was added, and the mixture was stirred for 10 minutes to obtain an oil phase;
[0089] (2) dissolving 0.5 parts by weight of Tween-20 and 1 part by weight of hexadecyltrimethylammonium bromide in 500 parts by weight of water to obtain an aqueous phase;
[0090] (3) The oil phase was added dropwise into the water phase, emulsified at 6000 r / min for 15 min, the pH value was adjusted to 9, heated to 40°C, stirred for reaction for 5 h, centrifuged, washed, and dried to obtain porous silica-coated zinc oxide.
[0091] The method for preparing the antibacterial ceramic brick in this example comprises the following steps:
[0092] (1) The porous silica-coated zinc oxide and the ceramic glaze were mixed in a mass ratio of 1:7, and then ball-milled with water for 20 minutes to obtain a glaze slurry;
[0093] (2) applying the glaze slurry obtained in step (1) on the green body layer, drying it, and firing it in a kiln at 1200° C. for 60 min to form a glaze layer without surface polishing;
[0094] (3) mixing the silver nitrate solution, the sodium citrate solution and perfluorooctyltriethoxysilane, stirring evenly, and then adding ethanol for dilution (the mass ratio of other raw materials to ethanol is 1:20) to obtain a mixed solution;
[0095] (4) The mixed solution obtained in step (3) is applied to the surface of the glaze layer in step (2), and is thermally cured at 150° C. for 1 hour to form a coating to obtain an antibacterial ceramic tile.
[0096] Comparative Example 1
[0097] The only difference from Example 1 is that the ceramic tile of Comparative Example 1 is not provided with a coating.
[0098] Comparative Example 2
[0099] The only difference from Example 1 is that Comparative Example 2 uses an equal amount of nano zinc oxide to replace the porous silicon dioxide-coated zinc oxide, and the other conditions remain the same as in Example 1.
[0100] Comparative Example 3
[0101] The only difference from Example 1 is that the coating preparation raw material of Comparative Example 3 uses nanosilver, no silver nitrate solution and sodium citrate solution are added, the amount of nanosilver used is the same as the amount of nanosilver obtained by completely decomposing silver nitrate in Example 1, and the other conditions remain consistent with Example 1.
[0102] Product performance testing
[0103] The ceramic tiles prepared in Example 1, Example 4 and Comparative Examples 1-3 were used as samples and the following tests were performed.
[0104] 1. Antibacterial and durability: According to the standard "JC / T897-2014 Antibacterial Performance of Antibacterial Ceramic Products", antibacterial tests were carried out on the upper left, upper right, lower left, lower right and middle of the sample and the antibacterial rate was recorded. The average antibacterial rate of the five directions was taken as the overall antibacterial rate of the sample; the antibacterial durability test process was: first, according to the standard "GB / T9266 Determination of Scrub Resistance of Architectural Paint Coatings", the surface of the sample was scrubbed with 5% sodium hypochlorite solution 500 times using a black pig brown brush, and then the overall antibacterial rate of the sample was tested as above. The test results are shown in Tables 1 and 2.
[0105] Table 1
[0106]
[0107] Table 2
[0108]
[0109] 2. Hydrophobic performance: The test was conducted using the German LAUDAScientific contact angle meter LSA60. The specific test process is as follows: the sample was cut into 50mm×50mm size, placed on the stage, and water was dropped on the sample surface using a syringe; the test software was opened, and the water droplets on the sample surface were photographed using a camera (with blue light as the light source), and the outline of the water droplets was simulated to calculate the average contact angle between the water droplets and the sample surface.
[0110] 3. Antifouling performance: Coal ash powder, water and cooking oil were uniformly mixed in a ratio of 1:1:0.2 to obtain mixed sewage. Three points were taken from each sample to measure the original reflection coefficient. The average was taken as the original reflection coefficient of the sample. The mixed sewage was evenly coated on the sample and dried for 2 hours at a temperature of 23°C and a humidity of 50%. The sample was evenly flushed with water at a 45-degree angle for 1 minute at a height of 20 cm from the sample. The sample was then dried at a temperature of 23°C and a humidity of 50% until the next day. Five cycles were performed. The reflection coefficient was measured again in the above manner and recorded as the final reflection coefficient. The reflection coefficient decrease rate was calculated by the following formula:
[0111] Reflection coefficient decrease rate = (original reflection coefficient - final reflection coefficient) / original reflection coefficient × 100%.
[0112] The test results of the above hydrophobic and antifouling properties are shown in Table 3.
[0113] Table 3
[0114]
[0115] Note: The smaller the reflection coefficient decrease rate, the better the anti-fouling performance.
[0116] It can be seen from the test results in Tables 1 to 3 that the ceramic tile samples prepared in Example 1 and Example 4 have good antibacterial properties, hydrophobic and antifouling properties, and good antibacterial and durable properties.
[0117] Compared with Example 1, the glaze layer of Example 4 was not polished, and the porous silica-coated zinc oxide was not fully exposed, resulting in a decrease in the antibacterial rate.
[0118] Compared with Example 1, the antibacterial, hydrophobic and antifouling properties of Comparative Example 1 are significantly reduced due to the lack of coating.
[0119] Compared with Example 1, Comparative Example 2 uses nano zinc oxide instead of porous silica-coated zinc oxide, which is easy to agglomerate in the glaze and easily damaged during firing. The antibacterial properties of various parts of the ceramic tile are uneven, and the overall antibacterial performance is significantly reduced. The generated nano silver is easy to fall off, and the durable antibacterial rate is reduced.
[0120] Compared with Example 1, the coating of Comparative Example 3 is prone to agglomeration due to the direct use of nanosilver, the antibacterial properties of the ceramic tile are uneven, the overall antibacterial properties of the ceramic tile are poor, and the nanosilver is easy to fall off, resulting in a decrease in the durable antibacterial rate.
[0121] In addition, the ceramic tiles prepared in Examples 1 and 4 of the present invention also have excellent antibacterial properties against Staphylococcus aureus, which are similar to the antibacterial properties of Escherichia coli, with no significant difference; the antibacterial, hydrophobic and antifouling properties of the ceramic tiles prepared in Examples 2 and 3 of the present invention are similar to those of Example 1, with no significant difference.
[0122] The preferred embodiments of the present invention are specifically described above, but the invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. An antibacterial ceramic tile, characterized in that: The antibacterial ceramic tile comprises a body layer, a glaze layer and a coating layer from bottom to top; The raw materials for preparing the glaze layer include porous silicon dioxide coated zinc oxide; The coating is formed by heat curing a mixed solution containing a silver nitrate solution, a sodium citrate solution and a fluorine-containing compound; The porous silica-coated zinc oxide is prepared by a preparation method comprising the following steps: mixing zinc oxide, an organic solvent and an organosiloxane to obtain an oil phase; mixing an emulsifier, a porogen and water to obtain an aqueous phase; Adding the oil phase to the water phase, emulsifying, adjusting the pH value to alkaline, heating, stirring and reacting to obtain porous silica-coated zinc oxide; The fluorine-containing compound comprises at least one of perfluorooctyl triethoxysilane, heptadecafluorodecyl trimethoxysilane, trifluoropropoxysilane, double-terminal hydroxyl fluorinated polysiloxane and dodecafluoroheptylpropyl trimethoxysilane; The organic solvent comprises at least one of dichloromethane, ethanol, butanol, ethylene glycol methyl ether and propylene glycol methyl ether; The organosiloxane comprises at least one of ethyl orthosilicate, methyl orthosilicate, propyl orthosilicate and butyl orthosilicate; The emulsifier comprises at least one of Tween-20, Tween-40, Tween-60 and Tween-80; The porogen includes at least one of hexadecyltrimethylammonium bromide, hexadecyldimethylbenzylammonium chloride and hexadecyltrimethylsodium bromide.
2. The antibacterial ceramic tile according to claim 1, characterized in that: The alkaline pH value is 9-10.
3. The antibacterial ceramic tile according to claim 1, characterized in that: The heating temperature is 40-45°C; the stirring reaction time is 5-7h.
4. The method for preparing the antibacterial ceramic tile according to any one of claims 1 to 3, characterized in that: The following steps are involved: preparing a glaze slurry containing porous silica-coated zinc oxide; Applying the glaze slurry on the green body layer, drying and firing to form a glaze layer; mixing the silver nitrate solution, the sodium citrate solution and the fluorine-containing compound to obtain a mixed solution; The mixed liquid is applied to the surface of the glaze layer and thermally cured to form a coating to obtain the antibacterial ceramic tile.
5. The preparation method according to claim 4, characterized in that: The temperature of the thermal curing is 100-200°C.
6. The preparation method according to claim 4, characterized in that: The method also includes the step of polishing the glaze layer.
7. Use of the antibacterial ceramic brick according to any one of claims 1 to 3 in the field of construction.
Citation Information
Patent Citations
Preparation method of hollow mesoporous silica antibacterial agent grafted with guanidine salt polymer
CN110313470A
Antibacterial ceramic tile and preparation method thereof
CN115073003A
Ceramic tile with antibacterial function and preparation method thereof
CN117247288A